Inflammatory bowel disease: beyond the boundaries of the bowel. (June 2011) - Actis, Giovanni C; Rosina, Floriano; Mackay, Ian R
Dysregulated inflammation in the gut, designated clinically as inflammatory bowel disease (IBD), is manifested by the prototypic phenotypes of an Arthus-like reaction restricted to the mucosa of the colon, as in ulcerative colitis, or a transmural granulomatous reaction, as in Crohn''s disease, or an indeterminate form of the two polar types. That the inflammation of IBD can trespass the boundaries of the bowel has long been known, with articular, ophthalmologic, cutaneous, hepatobiliary or other complications/associations –– some autoimmune and others not –– affecting significant numbers of patients with IBD. Also notable is the frequency of diagnosis of IBD-type diseases on a background of systemic, (mostly myelo-hematological) disorders, associated with alterations of either (or both) innate or adaptive arms of the immune response. Finally, cases of IBD are reported to occur as an adverse effect of TNF inhibitors. Bone marrow transplant has been proven to be the only curative measure for some of the above cases. Thus, in effect, the IBDs should now be regarded as a systemic, rather than bowel-localized, disease. Genome-wide association studies have been informative in consolidating the view of three phenotypes of IBD (ulcerative colitis, Crohn''s disease and mixed) and, notably, are revealing that the onset of IBD can be linked to polymorphisms in regulatory miRNAs, or to nucleotide sequences coding for regulatory lymphokines and/or their receptors. At the effector level, we emphasize the major role of the Th17/IL-23 axis in dictating the perpetuation of intestinal inflammation, augmented by a failure of physiological control by regulatory T-cells. In conclusion, there is a central genesis of the defects underlying IBD, which therefore, in our opinion, is best accommodated by the concept of IBD as more of a syndrome than an autonomous disease. This altered mindset should upgrade our knowledge of IBD, influence its medical care and provide a platform for further advances.